Development of a Filit Test Application for Physical Fitness Courses - Novi Wijaya; Iyakrus Iyakrus; Syafaruddin Syafaruddin; Wahyu Indra Bayu; Meirizal Usra; Herri Yusfi; Arizky Ramadhan; Kevin Octara (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2023)
This research aims to produce a physical test application in physical fitness courses as a learning resource for Physical Education and Health students, Faculty of Teacher Training and Education, Sriwijaya University. The type of research used is research and development (R&D). The population in this study was all fifth semester students (5) totaling eighty four students (84). The sample for the small-scale trial consisted of twenty-one students (30), the large-scale trial consisted of fifty-four students (54). The instruments in this research are data collection using validation sheets, questionnaires or questionnaires and student learning test results. Technical data analysis uses validity tests, practicality analysis and effectiveness analysis. Based on the research results obtained from this research, this physical test application is said to be very valid, seen from the validation results for the average score for all aspects of the assessment of 4.05 in the very valid category. From the student response questionnaire, this learning media was said to be practical to use by getting a practicality score of 3.70 in the very positive category. Based on the results of student learning tests, physical fitness learning media, namely as a learning resource for Physical Education and Physical Education students at FKIP Sriwijaya University, is said to be effective to use. The test results from the learning outcomes obtained 92.0% completeness which is included in the high category. From the results of this research, it was concluded that the application of the physical test in the physical fitness course for Physical Education and Health students at FKIP Sriwijaya University was declared very valid, in its use the application of the filit test was also said to be practical in the positive category and the application of the physical test was also effective for use as a support for activities the learning process in physical fitness courses is due to being in the high category.